Estuarine ecology - Day, John W. 1945- (Wiley-Blackwell, 2013)
"Estuarine Ecology, Second Edition, covers the physical and chemical aspects of estuaries, the biology and ecology of key organisms, the flow of organic matter through estuaries, and human interactions, such as the environmental impact of fisheries on estuaries and the effects of global climate change on these important ecosystems. The second edition of this respected textbook provides much-needed updates and new chapters covering key topics in estuarine ecology"-- Provided by publisher.